Clinical value of combined SHOX2 and RASSF1A methylation in lung cancer diagnosis across tissue and liquid biopsy samples: a systematic review and meta-analysis - Ting Wang; Jianguo Zhang; Jiayang Wang; Xiaoqun Dong; Qiushi Lin; Leiming Guo; Bo Zhang; Yue Cao; Yining Zhai; Mathhew Hadfield; Khan Hina; Abbas E. Abbas; et al. (Oncology Reviews, 2026)
Lung cancer remains the leading cause of cancer-related mortality worldwide, with poor prognosis in advanced stage diseases. Although early diagnosis has the potential to improve patient outcomes, current diagnostic methods remain suboptimal, highlighting the need for accurate molecular biomarkers. We systematically reviewed 49 studies to evaluate the diagnostic performance of SHOX2 methylation, RASSF1A methylation, and their combined panel for lung cancer detection. The combined SHOX2/RASSF1A methylation panel demonstrated a pooled sensitivity of 77.8% (95% CI: 72.3%–82.5%) and specificity of 89.0% (95% CI: 86.6%–91.1%), with an HSROC area under the curve (AUC) of 0.916. SHOX2 methylation alone yielded a sensitivity of 69.4% and specificity of 91.7%, whereas RASSF1A methylation showed lower sensitivity (45.7%) but the highest specificity (93.8%). Pairwise comparisons demonstrated that the combined panel significantly improved sensitivity compared with either SHOX2 or RASSF1A alone while maintaining specificity comparable to SHOX2, although lower than that of RASSF1A. Subgroup analyses showed that assay method and pathological subtype contributed to differences in pooled sensitivity, whereas leave-one-out sensitivity analyses confirmed the robustness of the pooled estimates. In conclusion, the combined SHOX2/RASSF1A methylation panel provides a more balanced diagnostic performance than either biomarker alone and represents a promising adjunctive approach for lung cancer detection. Future studies should focus on standardizing detection methods, integrating these biomarkers with other diagnostic modalities, and evaluating their diagnostic performance in early-stage lung cancer to further enhance their clinical utility.